The Implementation of Skimming and Scanning Strategies in Teaching Reading Narrative Text to the Tenth Grade Students of SMAN 21 SURABAYA (RETAIN, 2013)
Abstract Some students find that reading is not an easy activity. It is because reading covers several integrated components, such as vocabulary, grammar, pronunciation, decoding and comprehension. Nevertheless, students can overcome their difficulties when they receive the apropriate training from their teacher. The best service that teachers could provide is to teach them reading strategies that might help them become independent readers. Skimming and scanning strategies are offered to help the student read in more focused and efficient way. Educators have already admitted the effectiveness of using skimming and scanning strategies in enhancing the student’s reading comprehension. However, in some cases, the teacher cannot apply those strategies properly. As a result, these strategies are either ignored or not taught effectively. Therefore, the aims of this study are to describe how the teacher implements skimming and scanning strategies and to describe how the students’ response toward the implementation of skimming and scanning strategies in learning narrative text. As stated, reading covers several integrated components. Reading text needs some strategies to overcome the students difficulties. Skimming is strategy in which the reader is looking for the text to get the idea of a text. While Scanning is astrategy for quickly finding specific information in a text without reading the entire article. This study uses qualitative research as the research type. The subjects of this study are the English teacher and students of X Class in SMAN 21 Surabaya. Observation checklist, fieldnotes, and questionnaire are used to gain data. The results of the implementation of skimming and scanning strategies shows that the teacher was not fully successful in implementing skimming and scanning strategies in teaching reading narrative text. The reason because there were still some steps that were not applied by the teacher. While based on the questionnaire that have been answered by the students, it can be seen that the students’ response toward skimming and scanning strategies was good. Implementing skimming and scanning needs a long period of time and practices. The teacher needs to explore more about those strategies to complete the knowledge in implementing skimming and scanning strategies. It is also hoped that the students apply these strategies continously to maximize the use of skimming and scanning strategies. For the next researcher, this study is expected to be a meaningfulful reference in conducting another research related to skimming and scanning strategies. Kata Kunci: skimming strategy, scanning strategy, teaching reading, narrative text, tenth graders.